The "PERFECT" Call: Congressional Representation by Tweet in the Midst of the Ukraine Whistleblower Scandal. Issue 1 (January 2022) - McKee, Seth C.; Evans, Heather K.; Clark, Jennifer Hayes
In this article we examine every tweet congresspersons sent from the time the media broke the news of President Trump's fateful July 2019 phone call with Ukrainian President Zelensky up to a week after House Speaker Pelosi announced a formal impeachment inquiry. Our aim is to understand the type of rhetoric Members of Congress (MCs) engaged in with respect to what we call the Ukraine Whistleblower Scandal (UWS). It is evident from our analysis that Democrats were more likely to sound off on the UWS, which comports with the fact that it was a Republican President who got into trouble. Further, there are characteristics of MCs that make them more likely to frame and discuss the UWS in certain ways, like House Representatives holding law degrees or serving on one of the House committees investigating the UWS. Finally, in this age of hyper-polarized parties, party affiliation was consistently the most important factor shaping representatives' Twitter statements on the UWS. In historical perspective, the overriding importance of party affiliation is lamentable since the charges against President Trump were solemn and serious.